THE USE OF LANGUAGE EXPERIENCE APPROACH IN TEACHING READING FOR YOUNG LEARNERS: Exploratory Study in Speak Up! English Course Bandung - Rahayu, Dewi Syntiawati (2013)
Reading is one of the skills taught in English as a Foreign Language (EFL) classroom. Reading is one of the most fundamental skill that are inquired in learning language as it influences other general language skills like speaking, listening and writing (Mikulecky, 2004). This research introduces Language Experience Approach (commonly abbreviated as LEA) in teaching reading for young learners. The aims of this research were to find out the improvement of students' reading motivation after teacher implementing Language Experience Approach and to reveal teacher and students' responses toward the use of Language Experience Approach in teaching reading. This exploratory research was conducted at one of English course in Bandung and 6 students participated in the research. Observation, questionnaire and interview were employed to gain the data. The data were analyzed qualitatively and quantitatively. The findings of this research showed that: 1) Language Experience Approach helped students improve their reading motivation and comprehension; 2) the teacher responded positively toward the use of Language Experience Approach and 3) the students showed positive attitude and higher motivation in learning process. The results of this research confirm the researches by Wurr (2002) and Curran (2007) from United States and Musthafa (2010) and Suparti (2008) from Indonesia, which stress the advantages of implementing Language Experience Approach in teaching reading for young learners. Keywords: language experience approach, reading, motivation, reading comprehension